Topical Povidone-Iodine for Treatment of Giant Fornix Syndrome. Issue 5 (September 2019) - Vahdani, Kaveh; Rose, Geoffrey E.
Abstract : Over a 2-year period, a 68-year-old woman suffered multiple recurrences of left giant fornix syndrome during the repeated tailing of intensive topical steroids and antibiotics; she had also undergone surgery to reduce the left upper fornix. After a further recurrence during tailing of topical therapy for bilateral disease, treatment with 4 times daily preservative-free povidone-iodine 5% eyedrops was started—with a marked improvement of symptoms and signs within a week. The patient is maintained, symptom-free, on once-daily povidone-iodine drops and dexamethasone 0.1% drops. The dramatic improvement on topical povidone-iodine therapy might suggest that, as an initial therapy, this might be more effective than the previously-recommended regime of hourly potent topical steroids and antibiotics. Abstract : Preservative-free povidone-iodine 5% eyedrops rapidly controlled giant fornix syndrome in a patient who had multiple recurrences of the condition while tailing repeated courses of intensive topical steroids and antibiotics, and prior upper fornix-reduction surgery.